Esterification of sludge palm oil using trifluoromethanesulfonic acid for preparation of biodiesel fuel - Hayyan, Adeeb; Hashim, Mohd Ali; Mirghani, Mohamed Elwathig Saeed; Hayyan, Maan; Alnashef, Inas Muen (Springer, 2013)
Trifluoromethanesulfonic acid (TFMSA) was used to reduce the high free fatty acids (FFA) content in sludge palm oil (SPO). The FFA content of SPO was converted to fatty acid methyl ester (FAME) via esterification reaction. The treated sludge palm oil was used as a raw material for biodiesel production by transesterification process. Several working parameters were optimized, such as dosage of catalyst, molar ratio, reaction temperature and time. Less than 2% of the FFA content was the targeted value. The results showed that the FFA content of SPO was reduced from 16% to less than 2% using the optimum conditions. The yield of the final product after the alkaline transesterification was 84% with 0.07% FFA and the ester content was 96.7%. All other properties met the international standard specifications for biodiesel quality such as EN 14214 and ASTM D6751.